Toward Integrity and Integration of the Church(es) Relating to the State in the Secularized Cultural Context of Estonian Society - Meego Remmel (Religions, 2023)
Classical paradigms of the church-state relations may be reflected in how the church has tried to work and live out her integrity in different cultural-political contexts. The churches in Estonia have envisioned Christian integrity in relation to the state differently in different times and stages of societal and cultural development. One could distinguish the following four types of relationships: the conflict, the harmony, the two kingdoms, and the social servanthood. This article will focus on the characteristics of these relationship paradigms along with some personal, communal, and ecumenical examples in the sense of integrity of Estonian church-life from the last century to the present day when social servanthood seems to be most relevant.